PENGARUH ASAL JURUSAN DAN KOMPETENSI DOSEN TERHADAP PRESTASI BELAJAR MAHASISWA PRODI D III KEBIDANAN UNIVERSITAS WIRARAJA SUMENEP - Eva Nurhidayati (Wiraraja Medika : Jurnal Kesehatan, 2015)
BACKGROUND OF STUDY : Main problem faces education world nowadays is the lowlevel on University Student’s achievement. Origin major of the Student is one of the factorswhich influence on the educational achievement beside lecturer’s competence.RESEARCH METHODOLOGY : Research design use in this research is Cross sectionalas correlational analytic. While respondents population are 52 taken from third semesterstudents in D-III Faculty Of Midwifery Wiraraja University year 2013 – 2014. And instrumentuse to collect data is in form of Questioner. Further, the data is analyzed by using DoubleLinier Regression test.RESULT OF THE RESEARCH : Result of this research is known that there is significantinfluence between student’s origin major and the lecturer’s competence toward Universitystudent’s education achievement by t amount is more than t table on 3,642 > 2,920. So thereis influence between origin major toward student achievement with the probability less thanexpectation α on ρ< 0,05. Also there is influence between lecturer’s competence towardUniversity student’s education achievement with the probability less than expectation α on ρ<0,05.CONCLUSION : From the research it is concluded that there is influence betweenstudent’s origin majors and lecturer’s competence toward education achievement onuniversity student in D-III Faculty Of Midwifery Wiraraja University.Keyword : Origin Majors, Lecturer’s Competence, Educational Achievement